2019
DOI: 10.15828/2075-8545-2019-11-2-175-185
|View full text |Cite
|
Sign up to set email alerts
|

The inventions in nanotechnologies as practical solutions. Part II

Abstract: A brief review of patents is given. The research performed by scientists, engineers and specialists in the area of nanotechnologies and nanomaterials result in increased efficiency of construction, housing sector and adjacent fields of economy. For example, invention «Elastic conductive film on the basis of silver nanoparticles», according to experts, is of great interest for science and industry. This new type of electronics potentially can be applied in many fields, such as elastic sensor skin for robot devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…It can also be seen that the incorporation of nanosilica had a positive effect on the mechanical properties of cement mortars, by compacting their structure and improving the bond between the aggregate and the cement matrix. Various studies have shown that the incorporation of NS in a mixture accelerates cement hydration and composite hardening; resulting in higher early strength [7,19,24]. This was also reflected in this study, through the possibility of determining the 12-hour compressive strength of NS-modified specimens, after curing at 5 o C and 10 o C. Samples without the addition of nanosilica fell apart during the press test.…”
Section: Application Of Nanotechnologies and Nanomaterials • примененsupporting
confidence: 56%
See 1 more Smart Citation
“…It can also be seen that the incorporation of nanosilica had a positive effect on the mechanical properties of cement mortars, by compacting their structure and improving the bond between the aggregate and the cement matrix. Various studies have shown that the incorporation of NS in a mixture accelerates cement hydration and composite hardening; resulting in higher early strength [7,19,24]. This was also reflected in this study, through the possibility of determining the 12-hour compressive strength of NS-modified specimens, after curing at 5 o C and 10 o C. Samples without the addition of nanosilica fell apart during the press test.…”
Section: Application Of Nanotechnologies and Nanomaterials • примененsupporting
confidence: 56%
“…Recently, nanomaterials have received significant attention from researchers and industry, in regard to their potential as concrete admixtures [5]. This is evidenced by the rapid increase in the amount of patents as well as by the availability of the first commercial products using this technology [6,7]. Among nanomaterials, nanosilica has gathered particular attention.…”
Section: Introductionmentioning
confidence: 99%
“…• A new composite material, containing ferrum and graphene oxide compound [19]. • A method to produce nanoporous polymers [20].…”
Section: These Are Inventions In Nanotechnological Area That Can Be Imentioning
confidence: 99%
“…• Новый композитный материал, содержащий соединение железа и оксид графена [19]. • Способ получения нанопористых полимеров [20]. • Прочность и долговечность цементных растворов, содержащих нанокремнезем и мелкий заполнитель из отходов стекла [21].…”
Section: также представляют интерес для специалистов следующие изобреunclassified
“…Carbon materials [4][5][6], nanofibers [7,8], nanotubes [9][10][11][12], nanoparticles of metal and metal oxides [13,14], graphene [15][16][17][18], and graphene oxide [19], as well as electrically conductive polymers (polyaniline, polypyrrole, and PEDOT:PSS) [20] and environmentally friendly ionic liquids, such as tributyl(octyl) phosphonium bis(trifloromethanesulfonyl) imide [21], can be used as conductive or antistatic agents to reduce the electrical resistance of materials. Carbon nanotubes and graphene have a conjugated structure in which carbon atoms are in the state of sp 2 hybridization, which makes it possible to transfer an electron along the entire carbon chain and conduct an electric current.…”
Section: Introductionmentioning
confidence: 99%